Law Effect of Leave Notary in Implementation Position Based on the Act No. 2 of 2014 On Notary - Rizqi Agung Pratiwi; Siti Juwariyah; Munsharif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Notary is competent public authority or his duty is to make the deeds authentic. Notaries have the right to take leave in accordance with Law Notary. Leave notaries are leaving the work of notaries in some time officially to rest, take a vacation or to become public officials. The purpose of this study to analyze how the legal consequences leave notary on the implementation of office in accordance with Act No. 2 of 2014 concerning Notary, the legal position of notaries replacement which replaces the notary in the period of leave, challenges and solutions faced by a substitute notary in implementing the office notary supplants the leave period. Legal Theory used in this research is the theory of Responsibility and Theory of Rule of Law.The effects of this study indicate that there are no legal consequences for the notary who take leave, when he took a leave of absence he has appointed a substitute notary, if in the future in which no party feels aggrieved as a effect of his actions then Substitute Notary to be held responsible, even though they had quit his respective duties as Notary Public; Substitute notary legal position that replaces the notary in the period of leave is a substitute notary has authority as a notary as by UUJN; Challenges and solutions faced by a substitute notary in implementing the replaced notary office within the period of leave such as a lack of knowledge or ignorance, inexperience and lack of understanding. The solution is to appoint a substitute notary notaries, notary substitute must have the precautionary principle, accuracy and precision in implementing the notary office of his predecessor in the leave to avoid the occurrence of negligence in carrying out his post.Keywords: Effects; Leave Notary; Notary Substitute.